Plakoglobin: Role in Tumorigenesis and Metastasis - Zackie Aktary; Manijeh Pasdar (International Journal of Cell Biology)
Plakoglobin (γ-catenin) is a member of the Armadillo family of proteins and a homolog of β-catenin. As a component of both the adherens junctions and desmosomes, plakoglobin plays a pivotal role in the regulation of cell-cell adhesion. Furthermore, similar to β-catenin, plakoglobin is capable of participating in cell signaling. However, unlike β-catenin that has well-documented oncogenic potential through its involvement in the Wnt signaling pathway, plakoglobin generally acts as a tumor/metastasis suppressor. The exact roles that plakoglobin plays during tumorigenesis and metastasis are not clear; however, recent evidence suggests that it may regulate gene expression, cell proliferation, apoptosis, invasion, and migration. In this paper, we describe plakoglobin, its discovery and characterization, its role in regulating cell-cell adhesion, and its signaling capabilities in regulation of tumorigenesis and metastasis.